Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1896)
Demorest's Family Magazine August 1896. Vol. 32, No. 10. -- Hull House: The First Social Settlement of Chicago -- Weir of Hermiston -- The Fury of the Winds -- A Study of Major William McKinney -- Notable Women of Atlanta, Georgia -- "IK Marvel" At Home -- Women Who Foster Patriotism -- Society Fads -- Our Girls: A Glimpse of Wellesley -- Home Art and Home Comfort: How to Light the House in Summer -- Household: The Guest Room -- Sanitarian: Summer Care of Babies -- The World's Progress -- About Women - Demorest's Magazine Purchasing Bureau -- Mirror of Fashions: Review of Fashions - August --
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original prints, Valdosta State University Archives and Special Collections, March 2, 2017.
Keywords: Magazines; Periodicals; Fashion; Women's History; Dressmaking; Needlework; Homemaking; Travel; 1800s; 19th Century; Social History